Analysis of The Relationship Between The Implementation of The Behavior-Based Safety (BBS) Program and The Level of Employee Compliance With Occupational Safety Principles at PT. Angkasa Pura Logistics - Firdaus, Mochamad David Maulana; Novrizal, Ahmad; Ramadhan, Raihan Aliffathur; Irfan, Mochammad; Ariyakohir, Muhammad; Abizarga, Daffa Qhalby; Oroh, Valentino Rifai; Malik, Anis Rohmana (Riviera Publishing, 2024)
Based on data from the Ministry of Manpower (MoM) in 2023, the number of workplace accidents in Indonesia was recorded at 370,747 cases. The Behavior-Based Safety (BBS) program is an approach that focuses on human behavior and social relationships in the workplace. Its goal is to reduce the risk of accidents and work-related injuries by increasing awareness, involvement, and responsibility of employees towards their own safety and the safety of their colleagues. The research was conducted using a quantitative cross-sectional research method. Data collected provide an overview of the relationship between variables. A cross-sectional research design was used to collect data on the Behavior-Based Safety (BBS) program, the level of compliance with work safety behaviors, and work safety behaviors at PT. Angkasa Pura Logistics at a specific time. Data were collected using a questionnaire filled out by respondents. The variation in compliance level scores can be explained by 22.5% of the variation in BBS program scores, while the remaining 77.5% is explained by variation in other variables outside the research model. The variation in employee work safety behavior scores can be explained by 66.4% of the variation in BBS program scores and compliance level, while the remaining 33.6% is explained by variation in other variables outside the research model. There is a significant and meaningful relationship between the BBS program and compliance level. There is a significant and meaningful relationship between the BBS program and work safety behavior. There is a significant and meaningful relationship between compliance level and work safety behavior. There is a direct relationship between the BBS program and workplace safety behavior. Therefore, the Compliance Level intervening variable does not mediate the relationship between the BBS Program and Work Safety Behavior.